Penerapan Hukum Bagi Pelaku Aborsi Secara Ilegal - hanafi, Yusuf (Universitas Medan Area, 2025)
The enforcement of law concerning illegal abortion encompasses a range of criminal penalties outlined in the Criminal Code (KUHP) and other legislative frameworks. These legal actions are not only directed at the primary perpetrators, such as healthcare providers or individuals who perform abortions, but also extend to others involved, including parents or partners who assist or support the act. The purpose of this article is to examine the factors contributing to the occurrence of illegal abortions and the application of legal measures against those who commit them. The methodology employed in this study uses a normative approach, utilizing a literature review of relevant laws and court decisions. The findings reveal that although the legal framework imposes severe penalties on individuals involved in illegal abortions, various obstacles hinder effective law enforcement. These include lack of oversight, ineffective enforcement mechanisms, and socio-economic factors that contribute to the high prevalence of illegal abortion. Therefore, collaborative efforts are needed to raise legal awareness, improve regulations, and implement more compassionate strategies in addressing illegal abortion cases.